2010
DOI: 10.1002/jctb.2549
|View full text |Cite
|
Sign up to set email alerts
|

Gold nanoparticle formation using Shewanella oneidensis: a fast biosorption and slow reduction process

Abstract: BACKGROUND: The metal respiring bacterium Shewanella oneidensis has previously been used for reduction of Pd(II) into Pd(0) nanoparticles. This study investigated whether Shewanella oneidensis could also perform the reduction of Au(III) to Au(0). The kinetics of both the biosorption and reduction of Au(III) were studied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 31 publications
(35 reference statements)
3
35
0
Order By: Relevance
“…[74]. Intracellular precipitation of nanosized particles was also evidenced in respiring bacterium Shewanella oneidensis and similar particle sizes were obtained with living and heat-killed cells [75].…”
Section: Microorganisms and Bacteriamentioning
confidence: 77%
See 1 more Smart Citation
“…[74]. Intracellular precipitation of nanosized particles was also evidenced in respiring bacterium Shewanella oneidensis and similar particle sizes were obtained with living and heat-killed cells [75].…”
Section: Microorganisms and Bacteriamentioning
confidence: 77%
“…8 to 40 - [72] 40 Sargassum wightii 8 to 12 11 [73] 41 Thermonospora sp. 7 to 12 8 [74] 42 Shewanella oneidensis 5 to 10 8.4±0.7 [75] 43 Bile salts 4 to 30 10 [76] 44 Bovine serum albumin -2 [ 77] 45 Cholesterol phenoxy hexanoate 12 to 16 - [79] 46 Cucurbit [7]uril 6 to 22 10±1.6 [80] 47 Thiacalix [4]arene -13.5 [81] 48 β-Cyclodextrin 60 to 100 - [82] 49 Hydroquinone 17 to 25 20 [83] 50 2,3,5,6-Tetrakis-(morpholinomethyl)hydroquinone -170±17 [84] 24 20 relationship existing between the surface of the particles and the stabilizing agent. In this regard, the growth of gold nanocrystals persists as long as the crystallization sites are not blocked by the capping agent and as long as the gold (III) salt is available in the reaction medium.…”
Section: Discussionmentioning
confidence: 99%
“…It is interesting that in the case of bacterium Shewanella oneidensis at low concentrations of precursor there was exclusively intercellular formation of nanoparticles, and at high, predominantly deposition on walls of S. Oneidensis cells was observed, nanoparticles were rather coarse to 100 nm and more [63]. It is reported [64] also about deposition of Pd(0) in periplasmic space of S. Oneidensis (Fig.…”
Section: Vegetable Biomasses and Extracts As Reduction Agents Of Metamentioning
confidence: 86%
“…[63,64]. Addition of external donor of electrons was also required for synthesis of Pd nanoparticles with usage of Desulfovibrio desulfuricans [65] bacterium.…”
Section: Vegetable Biomasses and Extracts As Reduction Agents Of Metamentioning
confidence: 99%
“…As reduction occurred on the dried cell surface, it was suggested that such reduction was non-enzymatic [39]. FTIR spectroscopic studies were carried out to investigate the plausible mechanism behind the formation of the Pd NPs and the change of functional groups on the cell surface.…”
Section: Characterization Of Pd Np/p Pastoris Catalystsmentioning
confidence: 99%